Diagnosis of Business and Predictive Models of Bancruptcy Risk – A Model Design - Borlea, Sorin Nicolae; Achim, Monica Violeta (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
In this paper we propose the development of a deterministic model for diagnosis the business performances, based on the current needs imposed by the requirements of a sustainable development economy. The beginning of the XXIst century brings new approaches to organization performance, so performance begins to be defined according to the value it creates for all stakeholders. The proposed model is based on assessing a FESG score type (based on four pillars of sustainable development (Economic/Financial, Environmental, Social and Governance). So, we extend the Triple Bottom Line approach introduced by Elkington (2002) with Quadruple Bottom Line, by adding in our score besides the economic/financial, environmental and social dimensions, a fourth dimension which is corporate governance. Maximizing economic, social and environment performances can be done only in the context of good collaboration at the level of corporate governance structures through which conflicts of interest are diminished. In our model we used SWOT method (Strength, Weakness, Opportunities and Threats) combined with the evaluation grids method (based on Likert scale with five levels). Also we have in mind the credit rating methodology used by Standards & Poors or Fitch agecies.